THE ROLE OF INSTAGRAM AS AN INFORMATION DELIVERANCE TO THE CITIZEN BY THE PUBLIC RELATIONS OF SALATIGA CITY GOVERNMENT - Silvia Widya Kusumaningtyas; Zon Vanel (Expose: Jurnal Ilmu Komunikasi, 2019)
Social media is one type of new media that facilitates the process of communication among human. Social media makes it easy for users to communicate and share information in a wider range. At present, not only people use Instagram, but the government also needs to keep up with the time to participate in using Instagram as an online information media. Public Relations of the Salatiga Government is one of the public relations departments that uses Instagram as an online information media to provide information needed by the community. This research aimed to find out how the content of the information was  and how the role of instagram was as an information deliverance to the citizen by the public relations of Salatiga. Through qualitative methods research, data is collected by means of interviews and observations. The results showed that the Salatiga  Government Public Relations Instagram account had a role to increase brand awareness, connect many people and as a source of information/ business promotion.Public Relations of the Salatiga Government considers that Instagram plays an active role in conveying information to the public. This is seen from the many positive responses received by the Salatiga City Government Public Relations during managing Instagram as a modern information deliverance.